Acceptability and Nutrient Profile of Cocoa Fruit Peel-Based Cookies: Exploring a Functional Food Potential - Rita Irma; Risma Risma; Fonnie E. Hasan; Rosnah Rosnah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Cocoa (Theobroma cacao L.) is a valuable agricultural commodity that can be developed into diverse products with high economic potential. This study aimed to evaluate the sensory acceptability and nutrient composition of cookies formulated with cocoa fruit peel (Theobroma cacao L.) as a functional ingredient. Cocoa peel flour and cookies were analyzed for macronutrients (protein, fat, carbohydrates, fiber) and micronutrients (minerals, vitamins, flavonoids). Sensory evaluation was conducted using a hedonic scale on color, aroma, texture, and taste among 40 semi-trained panelists. Results showed that all formulations were generally acceptable, with the 10% cocoa peel substitution achieving the highest preference. Statistical analysis indicated significant differences in color and taste (p < 0.05), while aroma and texture showed no significant variation. Nutritional analysis confirmed that cocoa peel flour and cookies contained essential nutrients, including protein (9.46-9.75%), fat (5.14-9.35%), carbohydrates (46.48-55.37%), vitamins C and E, minerals (Fe, Ca, Zn), and flavonoids, although antioxidant levels decreased after baking. These findings highlight cocoa peel’s potential as a functional food ingredient, supporting sustainable utilization of cocoa by-products.